2011
DOI: 10.1038/ki.2010.488
|View full text |Cite
|
Sign up to set email alerts
|

Renalase deficiency aggravates ischemic myocardial damage

Abstract: Chronic kidney disease (CKD) leads to an 18-fold increase in cardiovascular complications not fully explained by traditional risk factors. Levels of renalase, a recently discovered oxidase that metabolizes catecholamines, are decreased in CKD. Here we show that renalase deficiency in a mouse knockout model causes increased plasma catecholamine levels and hypertension. Plasma blood urea nitrogen, creatinine, and aldosterone were unaffected. However, knockout mice had normal systolic function and mild ventricula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
177
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(185 citation statements)
references
References 36 publications
(41 reference statements)
6
177
1
1
Order By: Relevance
“…At variance with previous reports, we found that our protein, although eliciting the expected effects on blood pressure when injected into rats, was completely devoid of any amine oxidase activity [40]. At the same time, Desir and coauthors reasoned that, since the renalase sequence contains the dinucleotide binding motif GXGXXG, which is the hallmark of the Rossmann fold, it could bind either NAD or NADP [17,33,42]. Indeed, they found that in vitro refolded recombinant human renalase possesses NADH-oxidase activity, with a K m NADH of 15 ± 1 M, and a V max of 15 ± 0.1 nmol/min/mg, corresponding to a k cat of 0.40 min -1 [17].…”
Section: Functional Properties Of Renalasecontrasting
confidence: 83%
See 4 more Smart Citations
“…At variance with previous reports, we found that our protein, although eliciting the expected effects on blood pressure when injected into rats, was completely devoid of any amine oxidase activity [40]. At the same time, Desir and coauthors reasoned that, since the renalase sequence contains the dinucleotide binding motif GXGXXG, which is the hallmark of the Rossmann fold, it could bind either NAD or NADP [17,33,42]. Indeed, they found that in vitro refolded recombinant human renalase possesses NADH-oxidase activity, with a K m NADH of 15 ± 1 M, and a V max of 15 ± 0.1 nmol/min/mg, corresponding to a k cat of 0.40 min -1 [17].…”
Section: Functional Properties Of Renalasecontrasting
confidence: 83%
“…The main isoform (renalase 1, NP_001026879) is composed of 342 residues, with a theoretical molecular mass of 37,847 Da [7,8,15]. The orthologous mouse gene is annotated on chromosome 19C1 [16] and, as detailed in Chapter 7.1, it has been recently inactivated by homologous recombination, providing important experimental clues about its role in the modulation of the cardiovascular system [8,17].…”
Section: Structure Of the Renalase Genementioning
confidence: 99%
See 3 more Smart Citations